2002
DOI: 10.1007/s00420-002-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived odor and irritation of isopropanol: a comparison between naïve controls and occupationally exposed workers

Abstract: The results indicate that current exposure guidelines would be adequately protective of the acute adverse effect of nasal sensory irritation, as operationally defined by the intra-nasal lateralization threshold. Exposures to higher concentrations should perhaps be evaluated on the basis of existing knowledge about systemic, rather than local (e.g., irritation), toxic effects. IPA appears to be a weak sensory irritant and occupational exposure to IPA appears to elicit small changes in sensitivity that do not ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
1
13
0
3
Order By: Relevance
“…Studies of anosmic humans [12,17] have shown that phenethyl alcohol and vanillin mostly activate the olfactory nerve, CN I; but isopropyl alcohol [60] and l-menthol, like many olfactory stimuli, also activate the trigeminal nerve, CN V. Compared to extra controls (control bars at left of bars for extra stimuli in Fig. 4), correct identification of characteristic odors of extra compounds, with or without trigeminal epitope, increased by 18 % when added to the adapted mix.…”
Section: Mixture Component Identification Reveals Analytic Odor Prmentioning
confidence: 98%
“…Studies of anosmic humans [12,17] have shown that phenethyl alcohol and vanillin mostly activate the olfactory nerve, CN I; but isopropyl alcohol [60] and l-menthol, like many olfactory stimuli, also activate the trigeminal nerve, CN V. Compared to extra controls (control bars at left of bars for extra stimuli in Fig. 4), correct identification of characteristic odors of extra compounds, with or without trigeminal epitope, increased by 18 % when added to the adapted mix.…”
Section: Mixture Component Identification Reveals Analytic Odor Prmentioning
confidence: 98%
“…A few examples of ODTs and LTs obtained in the lab comparing previously exposed workers to subjects previously unexposed to a certain compound: (geometric) mean odor and irritation thresholds of 50 ppm and 15,682 ppm, respectively, for acetone were obtained by Wysocki et al (1997); 10 ppm and 8,874 ppm, respectively, for methyl iso-butyl ketone (MIBK) by Dalton et al (2000) and 11 ppm and 3,361 ppm, respectively, for isopropyl alcohol by Smeets and Dalton (2002).…”
Section: Methods Of Stimulus Presentationmentioning
confidence: 99%
“…This level would be low enough to protect the majority of people as they would not yet perceive irritation at that particular level. For example, in Smeets and Dalton (2002) the fifth percentile of LTs for IPA based on a sample of 52 subjects was determined at 400 ppm, which is equivalent to the threshold limit value in the USA, which is 400 ppm (ACGIH 1998). For MIBK, Dalton et al (2000) reported a fifth percentile of 1,802 ppm, and for acetone, 2,694 ppm, both of which are higher than their current allowable exposures and confirm that the current OEL based on irritation would be sufficiently protective.…”
Section: Can the Lateralization Threshold Help Determine An Oel?mentioning
confidence: 99%
See 1 more Smart Citation
“…Chamber studies testing formaldehyde at various fixed concentrations revealed that perceived irritation (nasal and ocular) increased with time during a 30-min exposure (Cain et al, 1986). In realistic daily home or occupational exposures to a chemical vapor that might be causing mild irritation, the nasal chemesthetic threshold for that chemical increases, revealing desensitization, but the effect does not appear to generalize to other irritants (Dalton et al, 2006;Smeets and Dalton, 2002;Wysocki et al, 1997). Exposures of two to three hours to mixtures of VOCs (Hudnell et al, 1992) and to the complex stimulus environmental tobacco smoke (Cain et al, 1987) revealed that the perceived intensity of chemesthesis clearly increases with time.…”
Section: I) Temporal Properties Of Nasal and Ocular Chemesthesismentioning
confidence: 99%